Alexandros Papadiamantis’ ’Vardianos sta sporka’: a new look in the light of the medical humanities - Menelaou, Iakovos (Research and Humanities in Medical Education, 2019)
One of medical humanities’ main goals, as it has emerged in recent years, is to promote and establish a more humane perspective in medicine. Doctors should focus on the patient and on his or her individual voice rather than on the disease. Through a study of Alexandros Papadiamantis’ novel ’Vardianos sta sporka’ (’Guardian of the Quarantined Ships’; 1893), I seek to show how this humane attitude is reflected in the German doctor in the story. The doctor, apart from utilizing the healing force of medicine, recognises the importance of faith and a mother’s care as important elements for recovery in a patient with cholera.